Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's analyze each statement given for the complex numbers [tex]\( x = a + b i \)[/tex], [tex]\( y = c + d i \)[/tex], and [tex]\( z = f + g i \)[/tex] to determine their truth values.
1. Commutativity of Addition:
[tex]\( x + y = y + x \)[/tex]
Addition of complex numbers is commutative:
[tex]\[ x + y = (a + bi) + (c + di) = (a + c) + (b + d)i \][/tex]
[tex]\[ y + x = (c + di) + (a + bi) = (c + a) + (d + b)i \][/tex]
Since addition in the real and imaginary parts is commutative, [tex]\( x + y = y + x \)[/tex] holds true.
This statement is true.
2. Associativity of Multiplication:
[tex]\( (x \times y) \times z = x \times (y \times z) \)[/tex]
Multiplication of complex numbers is associative:
[tex]\[ (x \times y) = (a + bi)(c + di) \][/tex]
By expanding, we get:
[tex]\[ (ac - bd) + (ad + bc)i \][/tex]
Similarly, we compute [tex]\( y \times z \)[/tex] and then multiply by [tex]\( x \)[/tex].
Without loss of generality, because each multiplication step follows associative properties, this leads us to the fact that:
[tex]\[ (x \times y) \times z = x \times (y \times z) \][/tex]
This statement is true.
3. Commutativity of Subtraction:
[tex]\( x - y = y - x \)[/tex]
Subtraction of complex numbers is not commutative:
[tex]\[ x - y = (a + bi) - (c + di) = (a - c) + (b - d)i \][/tex]
[tex]\[ y - x = (c + di) - (a + bi) = (c - a) + (d - b)i \][/tex]
Since [tex]\( a - c \neq c - a \)[/tex] and [tex]\( b - d \neq d - b \)[/tex], [tex]\( x - y \neq y - x \)[/tex].
This statement is false.
4. Associativity of Addition:
[tex]\( (x + y) + z = x + (y + z) \)[/tex]
Addition of complex numbers is associative:
[tex]\[ (x + y) + z = ((a + bi) + (c + di)) + (f + gi) = (a + c + f) + (b + d + g)i \][/tex]
[tex]\[ x + (y + z) = (a + bi) + ((c + di) + (f + gi)) = (a + c + f) + (b + d + g)i \][/tex]
Since both sides equate to [tex]\( (a + c + f) + (b + d + g)i \)[/tex], the property holds.
This statement is true.
5. Associativity of Subtraction:
[tex]\( (x - y) - z = x - (y - z) \)[/tex]
Subtraction of complex numbers is not associative:
[tex]\[ (x - y) - z = ((a + bi) - (c + di)) - (f + gi) = (a - c - f) + (b - d - g)i \][/tex]
[tex]\[ x - (y - z) = (a + bi) - ((c + di) - (f + gi)) = (a - c + f) + (b - d + g)i \][/tex]
Therefore, [tex]\( (a - c - f) + (b - d - g)i \)[/tex] does not equal [tex]\( (a - c + f) + (b - d + g)i \)[/tex].
This statement is false.
Based on the analysis:
- True: [tex]\( x + y = y + x \)[/tex], [tex]\( (x \times y) \times z = x \times (y \times z) \)[/tex], [tex]\( (x + y) + z = x + (y + z) \)[/tex]
- False: [tex]\( x - y = y - x \)[/tex], [tex]\( (x - y) - z = x - (y - z) \)[/tex]
1. Commutativity of Addition:
[tex]\( x + y = y + x \)[/tex]
Addition of complex numbers is commutative:
[tex]\[ x + y = (a + bi) + (c + di) = (a + c) + (b + d)i \][/tex]
[tex]\[ y + x = (c + di) + (a + bi) = (c + a) + (d + b)i \][/tex]
Since addition in the real and imaginary parts is commutative, [tex]\( x + y = y + x \)[/tex] holds true.
This statement is true.
2. Associativity of Multiplication:
[tex]\( (x \times y) \times z = x \times (y \times z) \)[/tex]
Multiplication of complex numbers is associative:
[tex]\[ (x \times y) = (a + bi)(c + di) \][/tex]
By expanding, we get:
[tex]\[ (ac - bd) + (ad + bc)i \][/tex]
Similarly, we compute [tex]\( y \times z \)[/tex] and then multiply by [tex]\( x \)[/tex].
Without loss of generality, because each multiplication step follows associative properties, this leads us to the fact that:
[tex]\[ (x \times y) \times z = x \times (y \times z) \][/tex]
This statement is true.
3. Commutativity of Subtraction:
[tex]\( x - y = y - x \)[/tex]
Subtraction of complex numbers is not commutative:
[tex]\[ x - y = (a + bi) - (c + di) = (a - c) + (b - d)i \][/tex]
[tex]\[ y - x = (c + di) - (a + bi) = (c - a) + (d - b)i \][/tex]
Since [tex]\( a - c \neq c - a \)[/tex] and [tex]\( b - d \neq d - b \)[/tex], [tex]\( x - y \neq y - x \)[/tex].
This statement is false.
4. Associativity of Addition:
[tex]\( (x + y) + z = x + (y + z) \)[/tex]
Addition of complex numbers is associative:
[tex]\[ (x + y) + z = ((a + bi) + (c + di)) + (f + gi) = (a + c + f) + (b + d + g)i \][/tex]
[tex]\[ x + (y + z) = (a + bi) + ((c + di) + (f + gi)) = (a + c + f) + (b + d + g)i \][/tex]
Since both sides equate to [tex]\( (a + c + f) + (b + d + g)i \)[/tex], the property holds.
This statement is true.
5. Associativity of Subtraction:
[tex]\( (x - y) - z = x - (y - z) \)[/tex]
Subtraction of complex numbers is not associative:
[tex]\[ (x - y) - z = ((a + bi) - (c + di)) - (f + gi) = (a - c - f) + (b - d - g)i \][/tex]
[tex]\[ x - (y - z) = (a + bi) - ((c + di) - (f + gi)) = (a - c + f) + (b - d + g)i \][/tex]
Therefore, [tex]\( (a - c - f) + (b - d - g)i \)[/tex] does not equal [tex]\( (a - c + f) + (b - d + g)i \)[/tex].
This statement is false.
Based on the analysis:
- True: [tex]\( x + y = y + x \)[/tex], [tex]\( (x \times y) \times z = x \times (y \times z) \)[/tex], [tex]\( (x + y) + z = x + (y + z) \)[/tex]
- False: [tex]\( x - y = y - x \)[/tex], [tex]\( (x - y) - z = x - (y - z) \)[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.